2015
DOI: 10.1111/jcmm.12598
|View full text |Cite
|
Sign up to set email alerts
|

‘Porosome’ discovered nearly 20 years ago provides molecular insights into the kiss‐and‐run mechanism of cell secretion

Abstract: Secretion is a fundamental cellular process in living organisms, from yeast to cells in humans. Since the 1950s, it was believed that secretory vesicles completely merged with the cell plasma membrane during secretion. While this may occur, the observation of partially empty vesicles in cells following secretion suggests the presence of an additional mechanism that allows partial discharge of intra-vesicular contents during secretion. This proposed mechanism requires the involvement of a plasma membrane struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…It could indicate that during embryonic development of the grass snake the content of zymogen granules was partially released to the intercalated ducts. This mode of secretion is connected with the incomplete fusion of the granule and cell membrane within the kiss‐and‐run mechanism, similarly as in humans (Jena, ).…”
Section: Discussionmentioning
confidence: 91%
“…It could indicate that during embryonic development of the grass snake the content of zymogen granules was partially released to the intercalated ducts. This mode of secretion is connected with the incomplete fusion of the granule and cell membrane within the kiss‐and‐run mechanism, similarly as in humans (Jena, ).…”
Section: Discussionmentioning
confidence: 91%
“…Nearly 38 trillion cells composing the human body communicate with each other via secreted biomolecules. In 1996, plasma membrane-associated 100-120 nm cup-shaped lipoprotein structures called porosomes were discovered in the exocrine pancreas and subsequently in the endocrine cells and neurons, that enable the secretion of biomolecules from cells (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that vesicle swelling is involved in the exocytotic process [1,2,3]. In secretory vesicles, a specific set of ion channels expressed in the membrane has been proposed to contribute to the secretory granule swelling [4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%